Legal regulation of the circulation of pyrotechnic products in Ukraine and administrative responsibility for its violation - K. L. Buhaichuk (Law and Safety)
The paper examines the regulations governing the circulation of pyrotechnic articles in Ukraine. The content of the Technical Regulation of Pyrotechnics, which came into force in January 2022, is revealed. These regulations determine the classes of pyrotechnic articles, the legal regime of their free circulation, the responsibilities of economic entities and their identification, labeling of pyrotechnic articles, the procedure for establishing the conformity of pyrotechnic articles, technical requirements for the safety of pyrotechnic articles. It is emphasized that the Technical Regulations establish age restrictions on the sale or transfer of pyrotechnic articles to persons under the age of: 12 years (class F1), 16 years (class F2), 18 years (class F3).